Cactus cladode polysaccharide as cryoprotectant in frozen Paneer (Indian Cottage Cheese). (5th August 2019) - Dey, Anirban; Rasane, Prasad; Singhal, Somya; Kumar, Vikas; Kaur, Sawinder; Singh, Jyoti; Garba, Umar; Kaur, Navneet; Arora, Mehak
Abstract : The study investigated the optimisation of freezing conditions for Paneer (Indian cottage cheese) incorporated with cactus cladode polysaccharide as cryoprotectant. The freezing rate of both natural and commercial cryoprotectant‐containing samples varied significantly. The optimised (2% natural cryoprotectant) Paneer sample had about 44% moisture content, 14% protein, 16% carbohydrate and 22% fat. Freezing time of optimised Paneer sample packed in metalised polyester was 40 min. The study concluded that Paneer incorporated with 2% cactus cladode polysaccharide, packaged using metalised polyester and frozen with packaged immersion freezing method, had the least freezing time (40 min) and retained better texture during freezing.